Empirical Study on Operational Efficiency in Retail Stores in Chandigarh Tricity - Choudhary, Himanshu; Sharma, Vandana (Prabandhan: Indian Journal of Management, 2009)
India’s organized retail sector is growing at a rapid pace. Some of the factors responsible for speeding up the growth of retailing in india are rapid urbanization, increase in disposable income, rising number of young qualified working professionals, easy availability of loans etc. Therefore, understanding and calculating operational efficiency of retail stores has become a significant concern to organized retailers. The present paper is an attempt towards this direction. The study has been conducted in Chandigarh Tricity (Chandigarh and its satellite cities of Mohali and Panchkula) keeping in view the dynamically growing organized retail here. The data of 200 retailers for the present research covers time frame from the year 2007 to 2008. After an extensive literature review it was pertinent that size of retail stores and their location played a significant role in measuring the operational efficiency of retail stores. An empirical analysis was conducted using chi-square test of independence to understand the role & contribution of type of retail formats on operational efficiency and to examine the impact of location on the same. It was concluded from the data analysis that there is significant influence of format of retail stores and location on the operational efficiency. However, the degree of association is not very high.